Solar Wind Plasma Interaction with Asteroid 16 Psyche: Implication for Formation Theories. Issue 1 (8th January 2018) - Fatemi, Shahab; Poppe, Andrew R.
Abstract: The asteroid 16 Psyche is a primitive metal‐rich asteroid that has not yet been visited by spacecraft. Based on remote observations, Psyche is most likely composed of iron and nickel metal; however, the history of its formation and solidification is still unknown. If Psyche is a remnant core of a differentiated planetesimal exposed by collisions, it opens a unique window toward understanding the cores of the terrestrial bodies, including the Earth and Mercury. If not, it is perhaps a reaccreted rubble pile that has never melted. In the former case, Psyche may have a remanent, dipolar magnetic field; in the latter case, Psyche may have no intrinsic field, but nevertheless would be a conductive object in the solar wind. We use Advanced Modeling Infrastructure in Space Simulation (AMITIS), a three‐dimensional GPU‐based hybrid model of plasma that self‐consistently couples the interior electromagnetic response of Psyche (i.e., magnetic diffusion) to its ambient plasma environment in order to quantify the different interactions under these two cases. The model results provide estimates for the electromagnetic environment of Psyche, showing that the magnetized case and the conductive case present very different signatures in the solar wind. These results have implications for an accurate interpretation of magnetic field observations by NASA's Discovery mission (Psyche mission) to the asteroid 16 Psyche. Key Points: Hybrid simulations of solar wind plasma interaction with magnetized or conductive asteroid Psyche Magnetized and conductive cases for Psyche show significant differences in solar wind interaction We provide predictions for Discovery mission to Psyche with implications for the formation history of Psyche